2000
DOI: 10.4049/jimmunol.165.8.4359
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Expression of β-Calcitonin Gene-Related Peptide in Rat T Lymphocytes and Its Significance

Abstract: Our previous data have shown that rat lymphocytes can synthesize calcitonin gene-related peptide (CGRP), a neuropeptide. In this study the type, characteristics, and functional role of lymphocyte-derived CGRP were investigated. The results showed that treatment with Con A (4 μg/ml) and recombinant human IL-2 (rhIL-2; 750 U/ml) for 3–5 days induced CGRP synthesis and secretion by lymphocytes from both thymus and mesenteric lymph nodes in a time-dependent manner. Stimulation of these cells with Con A (1–8 μg/ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 33 publications
3
30
0
2
Order By: Relevance
“…2). However, recent studies (2,3,42) reported that activated immune cells can produce neuropeptides such as SP, calcitonin gene-related peptide, and HT-29 monolayers were grown to confluence and then cultured in DMEM containing 0.1% FCS for 24 h. Cells were then incubated for an additional 3-24 h in medium alone or containing NT (10 Ϫ8 M). Total RNA was extracted, and 1 g was used to prepare cDNAs; COX-2 mRNA levels were determined by quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…2). However, recent studies (2,3,42) reported that activated immune cells can produce neuropeptides such as SP, calcitonin gene-related peptide, and HT-29 monolayers were grown to confluence and then cultured in DMEM containing 0.1% FCS for 24 h. Cells were then incubated for an additional 3-24 h in medium alone or containing NT (10 Ϫ8 M). Total RNA was extracted, and 1 g was used to prepare cDNAs; COX-2 mRNA levels were determined by quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…6B). SP and CGRP are released from sensory nerves when TRPV1 is activated, but they are also present in resident macrophages and circulating leukocytes (27)(28)(29). Indeed, SP treatment has been shown to stimulate macrophage- mediated phagocytosis in vitro (30).…”
Section: Trpv1 Deletion Affects Phagocytosis Via the Nk 1 Receptor Fomentioning
confidence: 99%
“…␣CGRP is produced mainly in the nervous system by the tissue-specific alternative splicing of the primary RNA transcript of the calcitonin/CGRP gene. On the other hand, ␤CGRP is produced not only in the neuronal tissues but also in the enteric nerves of the intestine (2) and in immune cells such as T cells (3). Pharmacologically, ␣CGRP is known to have the most potent vasodilatory activity (4).…”
mentioning
confidence: 99%